Foregrounding Draupadi, the Female Protagonist: Re-envisioning the Mahabharata in The Palace of Illusions - Payel Ghosh (PostScriptum: An Interdisciplinary Journal of Literary Studies)
Indian epics Mahabharata and Ramayana are transmitted orally from one generation to the next. Chitra Banerjee Divakaruni’s novel The Palace of Illusion, the retelling of Vyasa’s The Mahabharata has a uniqueness of its own. It takes us back to a time that is half history, half myth, and wholly magical. The great epic the Mahabharata is written from a male point of view and Draupadi’s voice has been neglected. All earlier versions written focused on male heroes and keep females backstage. With the rise of different psychoanalytic theories, feminist theories, cultural theories etc. writers began to reinterpret epic narratives and characters from new perspectives. Banerjee’s The Palace of Illusion is one such retelling of the Mahabharata that keeps Draupadi at the centre stage. Told in first person point of view, Divakaruni is recreating the epic from the perspective of Panchaali. The novel is about male domination, discrimination against women, their struggle, identity and position of women during the period of the Mahabharata. Draupadi’s life shows in the epic how women have to accept tradition and culture without any question. Draupadi tries to break the shackles of a stereotypical patriarchal society. Banerjee explores the rebel in Draupadi from the Mahabharata. Far from being docile and fragile, we see Draupadi as an iconoclast. This paper attempts to show how Draupadi encounters an existential crisis in the patriarchal hegemonic society and her quest for establishing her identity in that hegemonic structure. It also tries to parallelize the similarities between Banerjee’s Draupadi to that of contemporary women who quest against the shackles of tradition and convention. This study also analyses Draupadi’s feminine strength, and her complex relationships with Karna, Krishna and the palace. It also tries to portray myth and modernity clashing with each other to give birth to a new face.